The effect of traditional and improved solar drying methods on the sensory quality and nutritional composition of fruits: a case of mangoes and pineapples - Ssemwanga, M.; Makule, E.; Kayondo, S. (Elsevier, 2020)
Background This study investigated the effect of traditional and improved solar drying methods on the sensory quality and nutritional composition of the dried fruit products; using mangoes and pineapples, as a case study. The fruits were dried under five solar drying methods namely; open sun drying (OSD), black-cloth shade (BCS), white-cloth shade (WCS), a conventional solar dryer (CSD), and a newly improved solar dryer (ISD) technology. The ISD unit was made of a modified solar concentrator plate containing multiple metallic solar collectors arranged in series. The ISD drying cabinet was also enclosed with a specialized greenhouse cover materials. The drying operations were conducted following a completely randomized design (CRD) experimental procedure.